Availability of Financial Soundness Indicators - Slack, Graham (IMF Working Papers; Working Paper, 2003)
Because the wave of financial crises in recent years has spurred analysts' and policymakers' interest in monitoring the vulnerabilities of financial systems, the need for supporting data has increased. This paper presents survey results on the collection, compilation, and dissemination of data on a range of indicators of financial soundness in 100 countries. The paper distinguishes between the collection of financial soundness indicators for policymakers and their dissemination to the general public. It also explores the eagerness of national authorities to disseminate the information they collect and to what extent it relates to financial crisis experience.